Unconventional Raw Materials for Food Products - Dabija, Adriana; Codină, Georgiana Gabriela; Rusu, Lăcrămioara (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on applied research for the discovery of new raw material resources, for example, raw materials that can replace animal proteins and fats, sugar and salt, gluten from bakery products etc. The use of these unconventional raw materials in manufacturing recipes is a great challenge for specialists in the field, but also in terms of consumer acceptability and legislation in force. Additionally, this reprint presents some studies that have one thing in common: they all focus on finding new raw materials that can be used in food manufacturing recipes. These raw materials have been studied from a physicochemical, sensory, and food safety perspective.